High levels of Psoriasin (S100A7) and alfa-defensis in whole saliva from Down's syndrome patients - A. Sanna; E. Pisano; R. Boi; F. Iavarone; M..T. Sanna; T. Cabras; I. Messana (Journal of Biological Research, 2010)
-